Mickey Spillane's Kiss me deadly [videorecording (DVD)] - Saville, Victor, 1895-1979; Bezzerides, A. I. (Albert Isaac), 1908-2007; Aldrich, Robert, 1918-1983; Aldrich, Robert, 1918-1983; Meeker, Ralph, 1920-1988; Dekker, Albert, 1905-1968; Stewart, Paul, 1908-1986; Cooper, Maxine; Rodgers, Gaby; Leachman, Cloris; Spillane, Mickey, 1918-2006 (Criterion collection, 2011)
"In an atomic adaptation of Mickey Spillane's novel, directed by Robert Aldrich, the good manners of the 1950s are blown to smithereens. Snarling private detective Mike Hammer's decision one dark, lonely night to pick up a hitchhiking woman sends him down some terrifying byways. Brazen and bleak, it's a film noir masterpiece and an essential piece of cold war paranoia. Featuring as nervy an ending as has ever been seen in American cinema."--Container.